2020
DOI: 10.1155/2020/6364801
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Role of Cavin3 in the Progression of Lung Cancer and Its Mechanism

Abstract: Objective. The purpose of this study was to describe the role of Cavin3 in the progression of lung cancer and its underlying mechanism. Methods. Totally, 200 cases of lung cancer tissues and corresponding paracancer tissues were collected. Cavin3 expression in samples was determined by qRT-PCR, and the correlation with lung cancer stages as well as prognosis was statistically analyzed combined with matched clinical information. To investigate the mechanism of Cavin3 in lung cancer progression, firstly, Cavin3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In different studies, CAVIN3, perilipin 2 (PLIN2), pyruvate dehydrogenase kinase 3 (PDK3), lactate dehydrogenase C (LDHC), and E3 ubiquitin-protein ligase 2 (SIAH2) have been reported to be associated with the occurrence and development of various tumors and poor patient prognosis [32][33][34][35][36]. These markers are expected to be used as markers for targeted tumor therapy and prognostic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, CAVIN3, perilipin 2 (PLIN2), pyruvate dehydrogenase kinase 3 (PDK3), lactate dehydrogenase C (LDHC), and E3 ubiquitin-protein ligase 2 (SIAH2) have been reported to be associated with the occurrence and development of various tumors and poor patient prognosis [32][33][34][35][36]. These markers are expected to be used as markers for targeted tumor therapy and prognostic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer has become a public health concern worldwide (Sun et al 2020). Patients with lung cancer account for 11.6% of the total number of patients with cancer, and it is the leading cause of cancer deaths (Siegel et al 2019;Bray et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%